STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN LITERASI AL-QUR’AN PADA PESERTA DIDIK DI SMA ISLAM AL-MA’ARIF SINGOSARI - Nabila Nafisa Rahmawati; Moh. Eko Nasrullah; Adi Sudrajat (VICRATINA, 2022)
This dissertation discusses the policy of Islamic teachers in improving students' literacy in the quran with Al-maarif Singosari Islamic High School. The researcher directs this study to: what is the definition of quranic literacy, what is the PAI teacher's policy for increasing religious literacy among students, what is the effect of quranic literacy on students. This type of research is descriptive qualitative. The method used to collect data is field research such as observation, interview and documentation. The data analysis methods used are data reduction, data presentation and conclusion. The sources of data in this study were the teacher and students of PAI Al-Ma'arif Singosari Islamic High School. Based on the research results obtained by the researcher, it can be concluded that: 1) Writing the quran is an act of reading and writing the quran 2) The policy used by Islamic religious teachers to improve the quran. with the outside. Teaching Students The qur'an is through an approach to students and the practice of reading the qur'an before teaching. read quran